In Vivo Gastroprotective Effect along with Pharmacokinetics, Tissue Distribution and Metabolism of Isoliquiritigenin in Mice - Choi, Young Hee; Kim, You-Jin; Chae, Hee-Sung; Chin, Young-Won (Planta Medica, 2015)
As numerous herbal products have been used as dietary supplements or functional foods, the demands of the pharmacokinetic and pharmacodynamic characteristics of active compounds are increasing in order to secure a consistent outcome (i.e., efficiency and safety). In this study, the pharmacokinetics including tissue distribution, metabolism, and protein binding of isoliquiritigenin, a chalcone found in Glycyrrhiza glabra, and its metabolite, liquiritigenin, at various doses in mice are reported. Also, correlations between the preferential tissue distribution and pharmacological effect of isoliquiritigenin in certain organs were investigated using the in vivo gastroprotective effect of isoliquiritigenin in mice with indomethacin-induced ulcer. The absorbed fraction of isoliquiritigenin was high, but the absolute bioavailability was low mainly due to its metabolism. In spite of the low bioavailability, the gastroprotective effect of isoliquiritigenin was attributed to its high distribution in the stomach. Isoliquiritigenin prevented the occurrence of gastric ulcers by indomethacin, which is associated with increased gastric mucous secretion because the pretreatment with isoliquiritigenin presumably counteracted the decreased cyclooxygenase 2 by indomethacin. This may suggest that the pharmacokinetic properties of isoliquiritigenin are useful to predict its efficacy as a gastroprotective agent in a target organ such as the stomach.
Keywords: Glycyrrhiza glabra; Fabaceae; isoliquiritigenin; mice; pharmacokinetics; tissue distribution; gastroprotective effect